Affirmative action in Malaysia and South Africa: policies and outcomes in education and employment - Lee, H.A. (2010)
This paper surveys and evaluates affirmative action policies and outcomes in Malaysia and South Africa, two countries with majority-favouring regimes. I outline the historical contingencies and political economy of policy formulation, noting key similarities and differences. Broadly, Malaysia's continuity ofBumiputera political dominance and relatively discretionary policy framework contrasts with South Africa's post-Apartheid transition to democratic majority rule and institutionalization of a more statutory framework. This paper then presents empirical evidence of the progress of affirmative action, focusing on representation of disadvantaged groups in tertiary education and upper-level employment. We consider Malaysia and South Africa separately, followed by analysis of our findings in comparative perspective. On the whole, both countries have made quantitative gains in increasing representation of disadvantaged groups in targeted areas, but qualitative differences persist, especially in terms of the capacities of tertiary graduates from the beneficiary group and dependence on public sector employment. This paper concludes with discussion of policy proposals that emerge out of our analysis, particularly in view of the contrasting institutional frameworks of Malaysia and South Africa.